PHP 6 and MySQL 6 bible - Suehring, Steve (Bible., 2009)
"MySQL is the leading open source database on the market and PHP continues to dominate the server side of the scripting market--together, they are the most popular and common team for creating dynamic, database-driven web sites. This comprehensive book covers the newest version of PHP and MySQL and is packed with extensive code examples, full working applications, and valuable troubleshooting advice. You'll explore installing, developing, and debugging the latest versions of PHP and MySQL and get insight on advanced topics such as error handling, debugging, PEAR, security, HTTP, cookies, and OOP"--Resource description page.